Comparison of the Clinical Outcomes Between Isoperistaltic and Antiperistaltic Anastomoses After Laparoscopic Distal Gastrectomy for Patients With Gastric Cancer - Lee, Yoontaek; Lee, Chang Min; Park, Sungsoo; Kim, Jong-Han; Park, Seong-Heum (Frontiers in Oncology, 2020)
Background: No consensus exists regarding the superiority of either of the two types of gastrointestinal anastomosis, which are isoperistaltic and antiperistaltic. This study aimed to compare the clinical outcomes between isoperistaltic and antiperistaltic anastomoses after totally laparoscopic distal gastrectomy (TLDG) in patients with gastric cancer. Methods: We retrospectively reviewed the medical records of patients with gastric cancer who underwent TLDG with Billroth II anastomosis between January 2014 and December 2018. The patients were divided into two groups according to the peristaltic direction of gastrointestinal anastomosis after TLDG. One group underwent isoperistaltic anastomosis (Iso group), and the other underwent antiperistaltic anastomosis (Anti group). Clinical outcomes were compared between the groups. Results: Of the 148 patients who underwent TLDG with Billroth II anastomosis, 124 were included in the Iso group and 24 were included in the Anti group. The Anti and Iso groups showed no significant difference with regard to the incidence of internal hernia (0.0% vs. 6.5%, respectively; p = 0.355). The incidence of bile reflux was more frequent in the Iso group than in the Anti group (p = 0.010), but food stasis was more common in the Anti group than in the Iso group (p = 0.006). Conclusion: In gastric cancer patients who underwent TLDG in which postoperative adhesion was minimized, antiperistaltic anastomosis may have created a physiologic barrier in gastrointestinal continuity. However, a large-scale study is necessary to validate the relationship between the digestive stream and the peristaltic direction.